The Relationship Between Knowledge, Attitudes, and the Role of Officers with the Management of Household Wastewater Disposal (SPAL) in Hamlet II Teluk Mengkudu Serdang Bedagai - Meutia Nanda; Indah Rahayu Ritonga; Amelia Putri; Rizky Nanda Pratama (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
SPAL has several negative impacts that are not in line with health standards. When household wastewater seeps into the stream and ends up at ground level where it is discharged, the first thing to notice is to block the view. In addition, wastewater can also emit an unpleasant odor that makes it less comfortable for the community, especially those who are active indoors. In the coastal area of Dusun II, Sialang Buah Village, Teluk Mengkudu, Serdang Bedagai, the purpose of this study is to determine the relationship between knowledge, attitudes, and the role of health workers with the management of home wastewater drains. This study uses a cross-sectional quantitative research method. The sample was 53 respondents, representing 386 households and 1200 individuals. The research was conducted in Teluk Mengkudu, Serdang Bedagai, in Hamlet II, Sialang Buah Village. Random Sampling is a method used for sampling. The conclusion of the analysis shows that although knowledge and home SPAL are not related, the role and attitude of the officer are related to the household SPAL. To prevent the occurrence of diseases caused by wastewater sewers, it is hoped that the residents of Hamlet II, Sialang Buah Village, Teluk Mengkudu, Serdang Bedagai will further strengthen their awareness, attitudes, and activities regarding the correct household wastewater sewer (SPAL).